Investment portfolio management using the business cycle approach - Dzikevičius, Audrius; Vetrov, Jaroslav (Business: Theory and Practice, 2013)
A dissimilar performance characteristic displayed by asset classes over the economic business cycle has determined the purpose of this study - the integration of the business cycle approach into the construction of optimal investment portfolios. The paper combines business cycle, asset allocation and portfolio optimization theories by presenting a new model of the investment process and adding valuable information about the performance of asset classes in different phases of the business cycle. One of the best measures for the business cycle are leading indicators that can provide significant information on market expectations and future outlook; hence, every investor can improve his performance and risk management by adopting the results of this study. The use of the OECD Composite Leading Indicator as a business cycle measure assists in showing methods for constructing optimal portfolios and making investment decisions. The conducted analysis uses 6 asset classes: US stocks, EAFE stocks, Bonds, Gold, Real estate and Commodities. Monthly data on the performed research covers the period from February 1976 to December 2011.